2019
DOI: 10.3892/ol.2019.9976
|View full text |Cite
|
Sign up to set email alerts
|

Glypican‑3 expression in malignant small round cell tumors

Abstract: Malignant small round cell tumors usually progress rapidly and show resistance to chemotherapy, and it is often difficult to make a definitive diagnosis based on their histological morphology. Glypican-3 (GPC3) is a highly tumor-specific antigen, and the overexpression of GPC3 was reported in many pediatric and adult malignancies. In the present study, we investigated the GPC3 expression in pediatric malignant small round cell tumors to assess its role in the differential diagnosis of the tumors. Immunohistoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…It occurs mostly in the long bones and pelvis, and rarely in the kidney [ 1 , 2 ]. Small round blue cell tumors are histologically characterized by proliferation of small round tumor cells with sparse cytoplasm, which are often difficult to distinguish by standard histology or immunohistochemistry [ 3 , 4 ]. The disease usually has an insidious onset, rapid progress, easy recurrence and metastasis, and poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…It occurs mostly in the long bones and pelvis, and rarely in the kidney [ 1 , 2 ]. Small round blue cell tumors are histologically characterized by proliferation of small round tumor cells with sparse cytoplasm, which are often difficult to distinguish by standard histology or immunohistochemistry [ 3 , 4 ]. The disease usually has an insidious onset, rapid progress, easy recurrence and metastasis, and poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…In total, six surface antigens were identified as potential epitopes for RMS immunotherapy, including EGFR. A retrospective study using immunostaining of RMS patient samples ( Dobrenkov et al, 2016 ; Ganti et al, 2006 ; Grass et al, 2009 ; Majzner et al, 2019 ; Saraf et al, 2019 ; Shibui et al, 2019 ; Thway et al, 2011 ) revealed EGFR expression in a substantial fraction of human RMS ( n = 316 out of 476 primary patient samples and n = 9 of 12 cell line/PDXs; Fig. 6, B–D ; and Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al [ 33 ] reported that GPC-3 directly upregulated β-catenin to promote the proliferation and growth of lung squamous cell carcinoma. GPC-3 has also been reported to enhance the proliferation of nephroblastoma, hepatoblastoma, and melanoma cells [ 34 , 35 ]. In our study, we found the similar results that high GPC-3 expression levels were associated with tumor size and poor OS and DFS.…”
Section: Discussionmentioning
confidence: 99%